Heritage wheats of Georgia - Bedoshvili, D.; Mosulishvili, M.; Chkhutiashvili, G.; Chokheli, M.; Ustiashvili, N.; Maisaia, I. (The Journal of Nature Studies - Annals of Agrarian Science, 2020)
Georgia is characterized by remarkable diversity of the domesticated wheat. Five out of the fifteen wheat species found in Georgia, originate from Georgia and are local endemics. These wheat species are Triticum carthlicum Nevski, Triticum macha Dekapr. & Menabde, Triticum palaeocolchicum Menabde, Triticum timopheevii (Zhuk.) Zhuk., Triticum zhukovskyi Menabde et Eritczjan. T. carthlicum Nevski is free-threshing, while the other four wheats are hulled. The history of taxonomic identification, some specific morphological traits and the role they of these species in the ancient agriculture of Georgia are reviewed in the present paper. A traditional method of harvesting hulled wheats is also described and illustrated.